TRANSFORMASI FORMULASI MINYAK ATSIRI STIKESMAMBA’UL ULUM SURAKARTA BERSAMA CV.NATURONAL CREATAMA INDONESIA - Hardi Astuti Witasari; Kintoko Kintoko; Yusron Umar; Nova Rahma Widyaningrum Widyaningrum; Kiki Puspitasary; Meliana Novitasari (Jurnal Abdi Masyarakat Kita, 2026)
The use of essential oils extracted from plants as an alternative treatment is known as essential oils. This method has been proven to provide various health benefits. This collaboration created an integrated essential oils training program that aims to synergize academic knowledge with its application in the business world. This program was held to enrich participants' understanding and skills regarding the basic concepts of herbal business classes, essential oils making practices, and production process observations. Using a one-group pretest-posttest design approach, this activity summarizes the delivery of theoretical material, making essential oils products, and reviewing the production process in the factory. Based on the evaluation results, there was a significant increase in knowledge with an achievement rate of 90.34% in various aspects measured. Overall, this training successfully honed the technical competencies of participants while opening up opportunities for small-scale business startups in the field of essential oils products.